About peculiarities of self-bias voltage formation in plasma-chemical reactors with controlled magnetic fields - Hladkovskiy, V.V.; Fedorovich, O.A.; Polozov, B.P.; Kruglenko, M.P. (Вопросы атомной науки и техники, 2015)
The peculiarities of self-bias voltage formation in plasma-chemical reactors (PCR) with controlled magnetic fields have been investigated. The dependences of self-bias voltages on the values and configurations of magnetic fields in PCR, as well as, on the pressures, gas flows, discharge currents, discharge RF voltage drops are obtained. Экспериментально исследованы особенности образования напряжения автосмещения в плазмохимических реакторах (ПХР) с управляемыми магнитными полями. Получены зависимости напряжений автосмещения от величин и конфигураций магнитных полей в ПХР, а также от давлений, расходов газов, токов в разрядах, падений ВЧ-напряжений на разрядах. Експериментально досліджені особливості утворення напруги автозміщення в плазмохімічних реакторах (ПХР) з керованими магнітними полями. Отримано залежності напруги автозміщення від величин і конфігурацій магнітних полів в ПХР, а також від тисків, витрат газів, струмів у розрядах, падінь ВЧ-напруг на розрядах.